2014
DOI: 10.1021/ja510089c
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Activation of Organosilanes with η2-Aldehyde Nickel Complexes: Key for Catalytic Syntheses of Aryl-, Vinyl-, and Alkynyl-Benzoxasiloles

Abstract: An η(2)-aldehyde nickel complex was utilized as an effective activator for an organosilane in order to generate a hypervalent silicate reactant for the first time. This method was successfully applied to the highly efficient syntheses of 3-aryl-, vinyl-, and alkynyl-2,1-benzoxasiloles from benzaldehydes with aryl-, vinyl-, and alkynylsilyl groups at the ortho position. Initial mechanistic studies revealed that an intermolecular aryl transfer process was involved in the reaction mechanism. The formation of an η… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 82 publications
(19 reference statements)
1
27
0
Order By: Relevance
“…We have previously reported similar high barriers to rotation with a rhodium‐olefin system . Indeed, the metallaepoxide electromer of related nickel complexes have recently been invoked by the groups of Doyle and Ogoshi based on reactivity studies, and is also shown explicitly in Group 4 complexes that display similar structural parameters to the nickel species discussed here …”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…We have previously reported similar high barriers to rotation with a rhodium‐olefin system . Indeed, the metallaepoxide electromer of related nickel complexes have recently been invoked by the groups of Doyle and Ogoshi based on reactivity studies, and is also shown explicitly in Group 4 complexes that display similar structural parameters to the nickel species discussed here …”
Section: Introductionsupporting
confidence: 70%
“…Experimentally,t he 31 P{ 1 H} NMR spectrum of 1 up to 110 8Cr eveals no dynamic processes, indicatingt hat the barrier to carbonyl rotation is greater than 70 kJ mol À1 .W eh ave previously reported similar high barriers to rotation with ar hodium-olefin system. [8] Indeed, the metallaepoxide electromer of related nickel complexes have recently been invoked by the groups of Doyle [42] and Ogoshi [37] based on reactivity studies, andi sa lso shown explicitly in Group 4c omplexes that display similars tructural parameters to the nickel species discussed here. [58][59][60][61][62][63] Ambiguity in the electronic structureo ft hese nickel p-complexesh inderse fforts towards the rational design of nickel-catalysed processes.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…For example, we are exploring the organometallic chemistry of nickel, [10][11][12][13][14] which has undergone a renaissance in recent years. [15][16][17][18][19][20][21] Our focus has been the structure and reactivity of nickel π-complexes, which have been reported in a wide range of catalytic processes, including the coupling of CO 2 and ethylene, [5,[22][23][24][25][26][27][28][29][30][31][32] intermolecular Tischenko coupling, [33][34][35] benzoxasilole synthesis, [36,37] the aldol reaction, [38] allylic alkylation, [39] allylic amination, [40] allylic amidation, [41] epoxide functionalization, [42] and Suzuki-Miyaura coupling. [43] Nickel πcomplexes of heteroarenes have also been identified as key intermediates in nickel-catalysed catalyst transfer polycondensation to form polythiophenes.…”
Section: Introductionmentioning
confidence: 99%
“…14 In general, Si can form hypervalent silicates with Lewis bases such as F À or OH À , which are considered intermediate states in a variety of chemical reactions, owing to their high nucleophilicities. [15][16][17][18][19] Therefore, OH À is considered to play the same role as F À in CARE, as shown in Fig. 1(b), and to proceed an indirect dissociative adsorption of H 2 O, i.e., an indirect hydrolysis.…”
mentioning
confidence: 99%